1995
DOI: 10.1080/00288330.1995.9516691
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale spatial variation in growth, size at maturity, and yield‐ and egg‐per‐recruit relations in the New Zealand abaloneHaliotis iris

Abstract: Tag-recapture studies revealed differences in the growth rate of Haliotis iris between headlands and bays separated by as little as 200 m. Individuals off headlands had a significantly higher incremental growth and reached a higher maximum size than those in bays. These results were consistent with observations of the size composition of H. iris which showed that few individuals of harvestable size (> 125 mm shell length) were found in bays. Differences in the growth rate of H. iris may account for the apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Temperature has been suggested as a constraint that results in size clines of several species of abalone living in temperate waters (Lindberg 1992). The decline in size and abundance of black-foot abalone, Haliotis iris Martyn, in the warmer northern waters of New Zealand (Poore 1972;McShane & Naylor 1995) may be another example of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has been suggested as a constraint that results in size clines of several species of abalone living in temperate waters (Lindberg 1992). The decline in size and abundance of black-foot abalone, Haliotis iris Martyn, in the warmer northern waters of New Zealand (Poore 1972;McShane & Naylor 1995) may be another example of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these patterns in growth and size at maturity are commonly observed in abalone populations in Tasmania (Tarbath 2003), New South Wales (Worthington et al 1995a), Victoria (McShane et al 1988) and elsewhere in South Australia (Shepherd & Hearn 1983). These observations are probably a result of maturity being related to age, with blacklip in stunted areas maturing at the same age, but at a smaller size, compared to those in non-stunted areas (Shepherd & Laws 1974, Prince et al 1988, Shepherd et al 1991, Nash 1992, McShane & Naylor 1995. However, as we have no data on the age of individual blacklip in the present study, the observation of smaller size at maturity at stunted compared to nonstunted sites may reflect plasticity in the life-history strategy of blacklip among these areas (McAvaney et al 2004, Naylor et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that abalone in these protected areas grow more slowly, mature at smaller sizes and produce fewer eggs compared to individuals in more exposed habitats (Shepherd et al 1991, Wells & Mulvay 1995, Worthington & Andrew 1997. This variability is considered to be primarily a result of lower water movement providing less food in the form of drift algae (Day & Fleming 1992, Shepherd & Steinberg 1992, McShane & Naylor 1995. However, densitydependent processes, or genetic variability, may also contribute to relatively lower rates of growth in stunted areas, compared to other fished populations (Emmett & Jamieson 1988, Dixon & Day 2004.…”
Section: Abstract: Biological Variation · Morphometric Marker · Popumentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in New Zealand, the large sea urchin Evechinus chloroticus typically occupies deeper depth strata than the blackfoot abalone, Haliotis iris, which tend to aggregate in the shallow, wave-exposed subtidal (Schiel 1990, McShane andNaylor 1995). The two species are negatively associated at the scale of 25 m 2 in the shallow subtidal where their depth distributions overlap (Andrew and MacDiarmid 1999).…”
Section: Introductionmentioning
confidence: 99%